PERUBAHAN PENGGUNAAN LAHAN AKIBAT PENETAPAN RENCANA TATA RUANG WILAYAH (RTRW) KABUPATEN JEMBRANA TAHUN 2012 di WILAYAH DESA PESISIR , KABUPATEN JEMBRANA-BALI. - I Made Anggra Wijaya; I Nyoman Sukamara; Wayan Damar Windu Kurniawan (UNHI PRESS, 2020)
The coastal area in Jembrana Regency is part of the South Bali sea which stretches in the southern part of the Jembrana Regency region. The Regional Spatial Planning Document (RTRW) is prepared to be used as a guideline for land allotment in an area. This study aims to examine changes in land use in coastal villages in 2009 and 2017, analyzing land suitability between changes in land use that occur with the 2012 RTRW of Jembrana Regency. The results showed changes in paddy fields to residential land use and other buildings had an area of about 236.48 ha. Changes in dry land use to residential land use and other buildings have an area of 794.16 ha. The villages that experience land use changes include Melaya, Candikusuma, Tuwed, Banyubiru, Baluk, Penyaringan, Delod Berawah, and Perancak. based on the results of digitization and the results of observations of researchers the suitability of land use changes that occur mostly to building tourism accommodation and fisheries activities. Land use changes that occur in the cupel village, pengambengan, tegal badeng barat, tegal badeng timur, and lelateng that occur mostly become supporting buildings for fisheries activities.